Corporate Deductibility Provisions and Managerial Incentives - Marko Köthenbürger; Michael Stimmelmayr (Center for Economic Studies and ifo Institute (CESifo), 2013)
Using an agency model of firm behavior, the paper analyzes whether the cost of investment should be tax exempt. The findings suggest that, when managers engage in wasteful capital expenditures, welfare may decline if the cost of investment is tax deductible, as commonly advocated. The extent to which the return on investment should be taxed depends on how the internal provision of incentive pay and external monitoring by banks interact in constraining the manager and whether retained earnings or new share issues finance investments at the margin. The results are informative for the design of investment subsidies which might be integrated in corporate tax systems such as an Allowance for Corporate Equity or a cash-flow tax.
Keywords: H25; D21; 330; corporate taxation; investment subsidies; corporate governance; delegated monitoring; incentive contract